Electroacupuncture Pretreatment Attenuates Learning Memory Impairment Induced by Repeated Propofol Exposure and Modulates Hippocampal Synaptic Plasticity in Rats - Fan S; Wang X; Gao N; Wei S (Dove Medical Press, 2023)
Shunqin Fan, Xijun Wang, Ning Gao, Songli Wei Department of Anesthesiology, International Zhuang Medical Hospital Affiliated to Guangxi University of Traditional Chinese Medicine, Nanning, People's Republic of ChinaCorrespondence: Xijun Wang, Department of Anesthesiology, International Zhuang Medical Hospital affiliated to Guangxi University of Traditional Chinese Medicine, No. 8 Qiu Yue Road, Liang Qing District, Nanning, Guangxi, People's Republic of China, Email gzmzk01@163.comBackground: Recurrent propofol anesthesia in the peak of neurodevelopment may lead to learning-memory decline. This study aimed to examine the efficacy of electroacupuncture pretreatment in ameliorating the aforementioned learning memory deficits and to explore its underlying mechanisms in a rat model of repeated propofol exposure.Methods: 10-day-old Sprague Dawley rats were randomly assigned to five groups: the control, fat emulsion, propofol, electroacupuncture pretreatment and electroacupuncture pretreatment combined with propofol groups. The electroacupuncture pretreatment involved three consecutive daily sessions, while propofol was received intraperitoneally once daily for five days. Following the modeling period, the rats' learning-memory performance was assessed using the New Novel Arm Y-maze, New Object Recognition, and Morris Water Maze. The Nissl staining method was used to observe the development of hippocampal neurons, while Golgi staining was employed to observe hippocampal synaptic development.Results: The electroacupuncture pretreatment significantly attenuated the learning and memory impairment induced by recurring propofol exposure in rats. Additionally, it facilitated the development of hippocampal neurons and synaptic plasticity in the hippocampus. Immunofluorescence and Western Blot analyses were conducted to detect the expression of proteins related to apoptosis, learning memory, and synaptic plasticity. In the propofol group, the pro-apoptotic factors Caspase-3 and Bax was up-regulated, while the anti-apoptotic factor Bcl-2 was down-regulated, as compared to the blank group. Additionally, the phosphorylated cAMP-response element binding protein (pCREB), brain-derived neurotrophic factor (BDNF), synaptophysin, and growth associated protein-43 (GAP-43) was significantly decreased. In contrast, the electroacupuncture pretreatment combined with propofol group exhibited decreased the Caspase-3 and Bax and increased the Bcl-2, as compared to the propofol group, meanwhile, the pCREB, BDNF, Synaptophysin and GAP-43 was increased.Conclusion: Our findings indicate that electroacupuncture pretreatment can alleviate the learning and memory impairment induced by recurring propofol exposure in rats. This is achieved by enhancing hippocampal synaptic plasticity, activating the pCREB/BDNF pathway and inhibiting neuronal apoptosis.Keywords: electroacupuncture pretreatment, propofol, learning memory, synaptic plasticity